2019
DOI: 10.3389/fphar.2018.01542
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Response and Resistance to Cognitive Remediation in Schizophrenia: A Critical Review

Abstract: Cognitive impairment is a central feature of schizophrenia and has shown to play a crucial role in the psychosocial function of the disorder. Over the past few years, several cognitive remediation (CR) interventions have been developed for schizophrenia, whose effectiveness has also been widely demonstrated by systematic reviews and meta-analysis studies. Despite these evidences, many questions remain open. In particular, the identification of CR response predictors in patients with schizophrenia is still a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 94 publications
(219 reference statements)
2
20
0
1
Order By: Relevance
“…Similarly, Addington and Addington (2005) found an association between poor premorbid adjustment, increased negative symptoms and poorer social functioning (Quality of Life Scale) two years after the onset of schizophrenia. Barlati et al (2018) found in their review that cognitive remediation interventions seem to be more effective in schizophrenia patients with the following features: younger age, shorter duration of illness, few disorganized symptoms, greater pretreatment cognitive reserve and lower doses antipsychotics in their current treatment. This study support that higher CR is associated with greater response to cognitive rehabilitation.…”
Section: Premorbid Adjustmentmentioning
confidence: 99%
“…Similarly, Addington and Addington (2005) found an association between poor premorbid adjustment, increased negative symptoms and poorer social functioning (Quality of Life Scale) two years after the onset of schizophrenia. Barlati et al (2018) found in their review that cognitive remediation interventions seem to be more effective in schizophrenia patients with the following features: younger age, shorter duration of illness, few disorganized symptoms, greater pretreatment cognitive reserve and lower doses antipsychotics in their current treatment. This study support that higher CR is associated with greater response to cognitive rehabilitation.…”
Section: Premorbid Adjustmentmentioning
confidence: 99%
“…Indeed, the shared decision-making approach, taking into account patient's preferences, increases the motivation to treatment and, consequently, treatment adherence ( 174 183 ). In addition, it has been demonstrated that strong therapeutic relationships with a good therapeutic alliance are related to a decrease of symptom severity, hospitalizations, drop-out rates and to an increase in treatment adherence ( 48 , 183 , 184 ), while poor therapeutic relationships have been shown to increase the risk for non-adherence ( 40 , 43 , 185 ).…”
Section: Adherence To Treatmentmentioning
confidence: 99%
“…Different modalities and combinations of psychosocial interventions have been developed with the aim to address the complex individualized needs of patients ( 38 , 40 , 45 ), including the management of negative symptoms and cognitive dysfunctions ( 38 – 41 , 46 48 ), to improve patient's reintegration in the community, promote recovery, and support patients and their families ( 38 , 40 , 41 , 49 , 50 ). Some psychosocial interventions, such as psychoeducation and cognitive behavioral therapy (CBT), allow patients to gain knowledge about their illness; others, such as cognitive remediation, social skills training, and supported employment may enhance adaptive skills ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is possible that our sample was specific due to sociodemographic characteristics and prevalence of clinical symptoms (e.g., negative symptomatology, lack of insight) that can interfere with CR outcomes (for review see [58]). As we did not measure clinical symptoms during the intervention and our assumption is based merely on observation of the present therapist, we cannot draw any conclusions.…”
Section: Cognitive Assessmentmentioning
confidence: 99%